Better survival after surgery of the primary tumor in stage IV inflammatory breast cancer. (June 2020) - van Uden, D.J.P.; van Maaren, M.C.; Strobbe, L.J.A.; Bult, P.; Stam, M.R.; van der Hoeven, J.J.; Siesling, S.; de Wilt, J.H.W.; Blanken-Peeters, C.F.J.M.
Abstract: Introduction: Information regarding the effects of resection of the primary tumor in stage IV inflammatory breast cancer (IBC) is scarce. We analyzed the impact of resection of the primary tumor on overall survival (OS) in a large stage IV IBC population. Materials and methods: Patients diagnosed with stage IV IBC between 2005 and 2016 were selected from the Netherlands Cancer Registry, excluding patients without any treatment. To correct for immortal time bias, we performed a landmark analysis including patients alive at least six months after diagnosis. With propensity score matching, patients undergoing surgery of the primary tumor were matched to patients not receiving surgery. Multivariable Cox proportional hazard analyses were performed to determine the association between treatment strategy and OS in the non-matched and matched cohort. Results: Of the 580 included patients after landmark analysis, 441 patients (76%) received only non-surgical treatments and 139 (24%) underwent surgery (96% mastectomy). Median follow-up was 28.8 and 20.0 months in the surgery and no surgery group, respectively. Surgery in the non-matched cohort was independently associated with better survival (HR0.56[95%CI:0.42–0.75]). In the matched cohort (n = 202), surgically treated patients had improved survival over nonsurgically treated patients (p < 0.005). Multivariable analysis of the matched cohort revealed that surgery was still associated with better survival (HR0.62[95%CI:0.44–0.87]). Conclusion: Although residual confounding and confounding by severity cannot be ruled out, this study suggests that surgery of the primary tumor is associated with improved OS and should be considered as part of the treatment strategy in stage IV IBC. Highlights: The value of surgery of the primary tumor in stage IV IBC is still under debate. This nationwide study investigated whether surgery of the primary tumor in stage IV IBC is associated with overall survival. Surgery of the primary tumor in stage IV IBC was associated with improved overall survival· surgery of the primary tumor should be considered in stage IV IBC.